2012
DOI: 10.1111/cea.12012
|View full text |Cite
|
Sign up to set email alerts
|

Safety and predictors of adverse events during oral immunotherapy for milk allergy: severity of reaction at oral challenge, specific IgE and prick test

Abstract: CM-OIT was insufficiently safe in 25% of children. The above-mentioned clinical and immunological parameters would help clinicians to identify highly reactive patients before CM-OIT. In them, individualized schedules and premedication should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
73
1
13

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 37 publications
9
73
1
13
Order By: Relevance
“…Such omalizumab-enhanced OIT results are remarkable, given that in both studies the up-dosing phase was completed in a median time of 8 weeks and because both studies specifically included patients with high food-specific IgE levels, which normally correlate with desensitization failure [12][13][14]. A third study of omalizumab and OIT recently confirmed the usefulness of omalizumab in facilitating oral desensitization in milkallergic patients.…”
Section: Targeting Igementioning
confidence: 93%
See 1 more Smart Citation
“…Such omalizumab-enhanced OIT results are remarkable, given that in both studies the up-dosing phase was completed in a median time of 8 weeks and because both studies specifically included patients with high food-specific IgE levels, which normally correlate with desensitization failure [12][13][14]. A third study of omalizumab and OIT recently confirmed the usefulness of omalizumab in facilitating oral desensitization in milkallergic patients.…”
Section: Targeting Igementioning
confidence: 93%
“…It is estimated that >90% of patients undergoing oral desensitization develop reactions, and because of frequent allergic reactions, desensitization must be prolonged (1-2 years) before efficacious maintenance dosing can be achieved. In informahealthcare.comaddition, 10-30% of patients, generally those with higher initial food-specific IgE levels, have repeated reactions and are thus refractory to OIT [12][13][14]. Indeed, recent meta-analyses of oral desensitization studies suggest that the frequent serious adverse reactions might outweigh the benefits of OIT [15,16].…”
Section: Novel Therapiesmentioning
confidence: 99%
“…A pesar de los buenos resultados reportados en la mayoría de los pacientes (30,31), la tasa de abandono en el primer año ronda entre 10 y 40 % de los pacientes debido a síntomas usualmente leves o moderados, aunque también ocurren en ocasiones reacciones anafilácticas (32,33), por lo que dicha inducción debe hacerse bajo estricta vigilancia médica especializada. Debido a que actualmente no existen criterios aceptados de manera unánime sobre qué pacientes pueden recibir esta terapia, nosotros proponemos los criterios del cuadro 3 basándonos en nuestra experiencia y en la literatura actual disponible.…”
Section: Manejounclassified
“…Além disso, a história clínica do paciente deve ser considerada na interpretação do teste de alergia [11]. A determinação dos alérgenos mais comuns e a relação entre os resultados do TC com as doenças alérgicas em cada área desempenha um papel importante no diagnóstico e tratamento de doenças alérgicas, como no caso da imunoterapia [11,12].…”
Section: Introductionunclassified